2011
DOI: 10.1186/1745-6215-12-195
|View full text |Cite
|
Sign up to set email alerts
|

Illness management and recovery (IMR) in Danish community mental health centres

Abstract: BackgroundSchizophrenia and bipolar disorder are severe mental illnesses that can have a significant disabling impact on the lives of people. Psychosocial interventions that stress hope and recovery as a part of a multi-dimensional approach are possibly indicated to support people with severe mental illness in facilitating recovery. Illness Management and Recovery (IMR) is a curriculum-based psychosocial intervention designed as structured program with a recovery-oriented approach. The aim of IMR is to rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…I-IMR was associated with greater psychiatric illness self-management, consistent with prior randomized trials of IMR (1012,32,33). Our finding of improved self-management for diabetes but not for other general medical conditions is consistent with studies of older adults without mental illness.…”
Section: Discussionsupporting
confidence: 82%
“…I-IMR was associated with greater psychiatric illness self-management, consistent with prior randomized trials of IMR (1012,32,33). Our finding of improved self-management for diabetes but not for other general medical conditions is consistent with studies of older adults without mental illness.…”
Section: Discussionsupporting
confidence: 82%
“…This transition towards professional emancipation has resulted in experienced mental health nurses seeking post graduate education to enhance their skills, confidence and identity as effective practitioners. Today, a growing number of mental health practitioners including nurses' in the UK (Stern & Sin 2012), Australia (Mullen 2009), New Zealand (Crow et al 2010) and Denmark (Dalum et al 2011) value the broad panoply of skills, knowledge and framework that PSI provides for their practices. Today, a growing number of mental health practitioners including nurses' in the UK (Stern & Sin 2012), Australia (Mullen 2009), New Zealand (Crow et al 2010) and Denmark (Dalum et al 2011) value the broad panoply of skills, knowledge and framework that PSI provides for their practices.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the literature covered in this review may be seen as focusing on the task of exposing the mental health community to new knowledge, or disseminating such knowledge (Farkas & Anthony, 2007). Although it confirms findings that have previously emerged in the field, only a few examples describe experience with recovery-oriented methods (Färdig et al, 2011a(Färdig et al, , 2011bDalum et al, 2012). It is particularly important to avoid transforming the individual experience into a professionally defined method (Tew et al, 2011) there are many professional practices and system structures which can support the recovery process, as shown in the international Recovery research in the Nordic countries 567 literature (Leamy et al, 2011).…”
Section: Discussionmentioning
confidence: 61%
“…Of the seven articles covering quantitative studies, three were reports of randomised controlled trials conducted to evaluate the effects of recovery enhancing methods in outpatient psychiatry settings, in this case focusing on the Illness Management and Recovery programme (Dalum et al, 2012;Färdig et al, 2011aFärdig et al, , 2011b. Two of the others reported on cohort studies aimed at following up the extent of recovery in severe mental illness (Arvidsson, 2011;Lauronen et al, 2005), and one reported on a questionnaire study assessing recovery-oriented attitudes of three personnel groups involved in service provision (Klockmo et al, 2012).…”
Section: Resultsmentioning
confidence: 97%